Adolescence stage - its theories and characteristics - Kandouci, Saadia (Social Empowerment Journal, 2021)
The subject of our research deals with an important stage in the life of the individual, which is the stage of adolescence, which is one of the most important stages of human development, in which the adolescent is exposed to many problems and crises, and suffers conflicts and tensions, because it is the decisive stage in which sexual and moral emotions bear fruit and reach a state of maturity. A stage of transition between childhood and adulthood, from a phase in which he depends on others to a phase in which he relies on himself, and from a limited relationship within the family to an external social life on a larger scale. Through this scientific article, we try to identify the various theories that explain the stage of adolescence, while determining the age of this stage and revealing its psychological, social, mental and emotional characteristics.